PENGEMBANGAN MEDIA PEMBELAJARAN LUDO KING PADA MATERI MANUSIA SEBAGAI MAHLUK SOSIAL DAN EKONOMI DALAM MEMENUHI KEBUTUHANNYA - Ine Inengsih Riada; Yulita Puji Harti; Novi Eko Prasetyo; Loesita Sari; Budijanto Budijanto (IKIP Budi Utomo Malang, 2023)
As Millennial teachers, it is hoped that teachers can create media innovations to support quality learning in the classroom. There are many learning media that can be used in teaching and learning for teachers and students, so that students are excited about the learning process. On this occasion we developed Ludo King learning media to support the learning process in class with the subject of Humans as Social and Economic Beings in Fulfilling Needs. This game can be used as a student evaluation tool, but in a more fun way. The aim of this research is to develop Ludo King Learning Media on Human Materials as Social and Economic Beings in Meeting Their Needs in Class V11 IPS Students at SMP Negeri 1 Wewewa Barat” . This research method is research and development (R&D) using the 4D development model. The 4-D (Four D) development model consists of 4 main stages including: Define, Design, Development and dissemination. The results of research at SMP Negeri 1 Wewewa Barat can be concluded that there is a positive response to learning using ludo king media, this is indicated by the acquisition of media expert scores through questionnaires with a conversion level of achievement of 96.25% with a very valid category, acquisition of material expert scores through distribution questionnaire with a conversion level of achievement of 85.75% with a very valid category, acquisition of scores by linguists through distributing questionnaires with conversions of achievement levels of 93.25% with conversions of achievement levels of very valid category scores. The results of the evaluation of the questionnaire at the trial stage were distributed to 20 people students with the help of social studies subject teachers. Proving that learning media in the form of ludo is in great demand by students. This presentation is based on the results of a questionnaire evaluation which shows an interest level of 89.7% with the criteria of